2023
DOI: 10.1021/jacs.2c11107
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche-Inspired Genome Mining Leads to the Discovery of Crop-Protecting Nonribosomal Lipopeptides Featuring a Transient Amino Acid Building Block

Abstract: Investigating the ecological context of microbial predator−prey interactions enables the identification of microorganisms, which produce multiple secondary metabolites to evade predation or to kill the predator. In addition, genome mining combined with molecular biology methods can be used to identify further biosynthetic gene clusters that yield new antimicrobials to fight the antimicrobial crisis. In contrast, classical screening-based approaches have limitations since they do not aim to unlock the entire bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 88 publications
0
13
0
3
Order By: Relevance
“…For example, none of the five lipopeptide BGCs, which contain NRPSs with a characteristic N -terminal C domain, has been characterized or has homologous BGCs (Table ). A recent study has demonstrated the antifungal activity of bacterial lipopeptide keanumycins against plant pathogen Botrytis cinerea . These ThT22 lipopeptide BGCs may be a promising source for new antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, none of the five lipopeptide BGCs, which contain NRPSs with a characteristic N -terminal C domain, has been characterized or has homologous BGCs (Table ). A recent study has demonstrated the antifungal activity of bacterial lipopeptide keanumycins against plant pathogen Botrytis cinerea . These ThT22 lipopeptide BGCs may be a promising source for new antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated the antifungal activity of bacterial lipopeptide keanumycins against plant pathogen Botrytis cinerea. 72 These ThT22 lipopeptide BGCs may be a promising source for new antifungal agents. In addition, the BGCs we have discussed so far all have a core biosynthetic gene that has been used as the hallmark for the genome mining of natural products.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Structure elucidation of keanumycin D Our recent identication of keanumycins A-C proved to be helpful for structure elucidation of 1 (m/z 1122.5433 [M+H] + ). 22,43 Except for keanumycin C, all reported mycins are cyclic lipopeptides. Mild saponication 13 of 1 in MeOH led to the formation of compound with a mass increase of 32 Da (Fig.…”
Section: Nonribosomal Lipopeptides Protect Against Amoebal Predatorsmentioning
confidence: 99%
“…QS1027 uses a combination of structurally related CLPs, keanumycins and jessenipeptin, to overcome grazing by the model social amoeba Dictyostelium discoideum. 22 Interestingly, it has been hypothesised that predation resistance is linked to phytopathogen-suppressive traits, opening potential application in agricultural systems. 23,24 A good example is the work on CLPs of the amphisin family.…”
Section: Introductionmentioning
confidence: 99%
“…Đầu năm 2023, một tài tử đã khiến cho cả tạp chí khoa học lừng danh Nature phải sớm reo hò cổ vũ, huyên náo cả văn đàn học giới [1]. Nguyên do là từ một nghiên cứu mới xuất bản trên Tạp chí Hiệp hội Hóa học Mỹ (JACS) trong đó các nhà nghiên cứu đã phát hiện được một số hợp chất hóa học do vi khuẩn tổ hợp được, có sức mạnh hạ gục nhanh, tiêu diệt gọn nhiều loại nấm, bao gồm cả những loại gây thối hỏng hoa quả, thực phẩm [2].…”
unclassified